UAV-UGV cooperative targeted spraying system for honey pomelo orchard - Chen, Yuli; Liu, Zibo; Lin, Zhen; Xu, Zifeng; Guan, Xianlu; Zhou, Zhiyan; Zheng, Dateng; Hewitt, Andrew (International Journal of Agricultural and Biological Engineering, 2024)
To enhance adaptability in orchards with taller average tree heights and improve spraying effectiveness on Jinggang pomelo trees, this paper proposes a UAV-UGV cooperative targeted spraying system (UCTSS) and develops a prototype. The UCTSS primarily consists of a UAV and a UGV, networked using the Robot Operating System (ROS). During operation, boththe UAV and UGV navigate between tree rows while carrying the spraying module. When the UAV reaches suitable spraying positions, the UGV halts to activate the spraying module, and the UAV performs targeted spraying from top to bottom. The paper employs a master-slave method for basic formation control of the UAV and UGV, resulting in an average tracking errorof 0.118 m and a standard deviation of 0.040 m during testing. Additionally, a LiDAR-based targeted spraying detection method is designed and validated through simulation experiments, achieving an accuracy rate of 96% with an average position error of 0.13 m. Field trials in orchards demonstrate that the UCTSS meets stability requirements, with the average tracking error of the UAV measuring 0.158 m during coordinated movement and 0.013 m during spraying. In terms of spraying effectiv-eness, the UCTSS exhibits higher average droplet density and deposition values at various heights of the same tree compared tothe DJI-T50, along with a lower coefficient of variation between levels, resulting in a more uniform spraying effect. The feasibility of the UCTSS is validated, providing a novel approach for orchard protection in areas with taller average tree heights.Keywords: plant protection, UAV-UGV cooperation, orchard, master-slave, targeted spraying, LiDARDOI: 10.25165/j.ijabe.20241706.8989Citation: Chen Y L, Liu Z B, Lin Z, Xu Z F, Guan X L, Zhou Z Y, et al. UAV-UGV cooperative targeted spraying system for honey pomelo orchard. Int J Agric & Biol Eng, 2024; 17(6): 22–31.